A Note on the Finite Element Method for the Reissner-Mindlin Plate (Journal of Computational Mathematics, 1994)
In this short note we use the idea of R. Duran [5] and introduce a new low-order traiangular element by replacing the nonconforming linear element for the rotation in [2] with the conforming linear element. The optimal order error estimates are obtained uniformly in the plate thickness.